Public health services and adjustments with third sector entities: an integrative review - Nóbrega, Joanacele Gorgonho Ribeiro; Dantas, Jamily Ribeiro Marques; Nóbrega, Jânio Meira; Sousa, Carmelita Maria Silva; Feijo, Nathassya Nauany Silva Pinheiro; Sousa, Allex Alves Sobral de; Querino, Monalisa Martins; Santana, Willma José de (Brazilian Journal of Production Engineering, 2021)
The growth of the third sector in Brazil is explained by the pressures of society in relation to the minimum State in the search for basic rights and by the State’s intention to pass on to society the services in several sectors in which it is unable to provide due assistance with regard to the quality and meeting health demands. The emergence of the third sector served to bridge the gap between the public and private sectors. With the inoperability of the State, it emerged with the objective of generating services of a public nature, through the help of the private sector. The Third Sector is believed to be a great partner for the governments: Federal, State and Municipal. The aim of this study was to verify public health services and the adjustments made with third sector entities in the current literature. This is an integrative literature review. The selection of studies was the search for publications indexed in databases. A total of 27 articles were selected, of these, 14 met the pre-established criteria. However, it is understood that the Third Sector is capable of making the right to health effective since the state is notoriously incapable of meeting all demand, be it qualitative or quantitative, it is known that, due to lack of personnel, whether due to lack of resources, in addition to other variables such as improbity and corruption, there are huge queues, lack of beds in the ICU, inability to treat more complex diseases and even a lack of more basic materials to live up to the most common health needs of the population. - by the way, the article is even scandalized in the daily media.